Hubungan Tingkat Pengetahuan Terhadap Kepatuhan Minum Obat Antihipertensi Di Rumah Sakit Umum Daerah Pringsewu - Munawaroh, Iis Hapson; Pratiwi, Mida; Putri, Diah Kartika; Yanti, Erna (Jurnal Ilmiah Wahana Pendidikan, 2025)
Blood pressure ≥140/90 mmHg is considered hypertension, and by 2025, there will likely be 1,6 billion hypertensive individuals worldwide. Medication non-compliance is the cause of the rise in the incidence of hypertension. As a result, there is very little chance of success in lowering the number of people with hypertension. One of the top 10 ailments in the Pringsewu district is hypertension. An increasing number of patients at Regional Hospital OF Pringsewu have hypertension each year. The research objective was to determine the knowledge level and compliance with taking antihypertensive medication at the Regional Hospital of PringsewuThis type of quantitative analytical research is a cross sectional approach. The sampling technique is purposive sampling method. Data analysis using Chi-Square. The sample of hypertension patients at the Regiona Hospital of Pringsewu was 91 respondents who met the inclusion criteria. The research results showed that 54% of respondents had good knowledge, 26.4% of respondents had sufficient knowledge, 18.7% of respondents had poor knowledge, 45.1% of respondents had high compliance, 19% of respondents had moderate, 35.2% of respondents had low compliance. Analysis of the correlation between knowledge and compliance in taking medication using Chi-Square shows that there is a correlation between the level of knowledge and adherence to taking medication with a p-value = 0.000 (p<0.05). Conclusion: The knowledge level of hypertension patients was in the good category and compliance was in the high category. There is a correlation between the knowledge level and compliance with taking hypertension medication at the Regional Hospital of Pringsewu